Penerapan Media Telepathy Game sebagai Strategi Pembelajaran Inovatif dalam Pengajaran Pendidikan Agama Islam di SMP Negeri 22 Surabaya - Ayatillah, M. Ishom Fahmi; Auliya', Hilyatul; Maulida, Anis Yuni; Syafi'i, Imam; Farichah, Siti (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
The purpose of this study describes the application of telepathy game media as an innovative learning strategy in teaching Islamic Religious Education at SMP Negeri 22 Surabaya. Field research methods are directly applied in direct observation to monitor developments in improving innovation in Islamic religious education learning. The results of the study show that many strategies are owned by teachers in using innovative learning media, especially Islamic Religious Education learning, so it is easier for students to receive learning. The use of telepathy game media in Islamic religious education lessons is more effective.